Major Insect Pests and Pesticide Use Practices among Tomato Growers in Kathmandu and Bhaktapur Districts - Gauli, K.; Sah, L.P.; Shrestha, J.B.; Rajbhandari, B.P.; Ghimire, A.R. (Journal of the Plant Protection Society, 2020)
Abstract available with the full text.